1969
DOI: 10.1037/h0028257
|View full text |Cite
|
Sign up to set email alerts
|

Social class differences in maternal teaching strategies and speech patterns.

Abstract: The study was designed to explore social class differences in maternal behavior in both structured and unstructured mother-child interaction situations, and in an interview. Seventy-six lower-class mothers were compared to 38 middle-class mothers in an unstructured "waiting-room" situation, and in a structured problem-solving situation with the child. In addition, all mothers were interviewed and certain features of their language analyzed. Significant social class differences in maternal behavior appeared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0
1

Year Published

1973
1973
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(58 citation statements)
references
References 7 publications
5
52
0
1
Order By: Relevance
“…Studies of language development in typically developing children find significant differences in the quantity and quality of caregiver speech children receive (e.g., Bee, Van Egeren, Streissguth, Nyman & Leckie, 1969; Farian & Haskins, 1980; Hart & Risley, 1995; Hoff, 2003; Huttenlocher, Vasilyeva, Waterfall, Vevea, & Hedges, 2007; Rowe, Pan & Ayoub, 2005), which are often correlated with background characteristics, such as socioeconomic status (SES). These input differences appear to be related to vocabulary growth (Hart & Risley, 1995; Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1991; Pan, Rowe, Singer & Snow, 2005) and growth in sentence length (Barnes, Gutfreund, Satterly, & Wells, 1983) and complexity (Huttenlocher et al, in prep).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of language development in typically developing children find significant differences in the quantity and quality of caregiver speech children receive (e.g., Bee, Van Egeren, Streissguth, Nyman & Leckie, 1969; Farian & Haskins, 1980; Hart & Risley, 1995; Hoff, 2003; Huttenlocher, Vasilyeva, Waterfall, Vevea, & Hedges, 2007; Rowe, Pan & Ayoub, 2005), which are often correlated with background characteristics, such as socioeconomic status (SES). These input differences appear to be related to vocabulary growth (Hart & Risley, 1995; Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1991; Pan, Rowe, Singer & Snow, 2005) and growth in sentence length (Barnes, Gutfreund, Satterly, & Wells, 1983) and complexity (Huttenlocher et al, in prep).…”
Section: Introductionmentioning
confidence: 99%
“…ences across families within a particular culture (Bernstein, 1970;Diaz, Neal, & Vachio, 1991;Ninio, 1980). Middle-class parents have been reported to conform to authoritative or progressive beliefs compared to low-income parents who are seen as authoritarian, negative, and restrictive (Bee et al, 1969;Bernstein, 1970;Laosa, 1980). This assumption is clearly challenged by these discussions.…”
Section: Leadermentioning
confidence: 88%
“…Distinct from both of the previous patterns, the permissive parent makes few demands of the child, preferring to be a resource to the child, rather than an active agent responsible for shaping or altering the child's ongoing or future behavior. Several studies have reported strong associations between these beliefs and parental teaching strategies in both structured and unstructured tasks with children (Bee, Egeren, Streissguth, Nyman, & Leckie, 1969;Schaefer & Edgerton, 1985 An understanding of the beliefs of culturally diverse families, then, could lead to more effective parent education programs that build on parent strengths and needs. This may be especially important for developing specialized services for high-risk groups, such as teenage mothers and their children, which is the focus of this research.…”
mentioning
confidence: 98%
“…While evidence abounds to support the theories that social class and/or ethnicity are significantly related to differences among parent groups in patterns of child rearing (Havighurst & Davis 1969;Sears, Maccoby, & Levin 1957), maternal teaching strategies (Bee, Egeren, Streissguth, Nyman, & Leckie 1969;Hess & Shipman 1965, 1967, linguistic mode (Bernstein 1961(Bernstein , 1964, and values (Kohn 1969), few direct comparisons of the behavioral expectations of parent and teacher have been made. Indeed, existing studies are marked by contradictory findings with regard to the expectation that parents and teachers will differ from each other in their behavioral expectations of children and by inconsistencies in the treatment of the variables examined.…”
Section: Comparisons Of the Expectations Of Parentsmentioning
confidence: 99%